2021
DOI: 10.3389/fpsyg.2021.724126
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Is Associated With Lower Stress and Higher Work Engagement in a Large Sample of MOOC Participants

Abstract: Objective: This study aimed to understand the associations between mindfulness, perceived stress, and work engagement in a very large sample of English-speaking adults, from 130 different countries. It also aimed to assess participants' self-reported changes following a 6-week mindfulness massive open online course (MOOC).Methods: Participants in the 6-week MOOC were invited to complete pre-post online surveys. Cross-sectional associations were assessed using univariate linear models, followed by structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 82 publications
0
14
1
Order By: Relevance
“…In the subtheme of "channeling attention into productivity", participants found focusing on the present task, regulating responses to deadlines, unitasking and efficiently switching attention, all improved their productivity. Other studies, including a prior study of the MWPP, recognized improvements that mindfulness can bring to productivity (26). A workplace MBI improved team and organizational "climate" and individual performance with greatest improvements seen in co-operation between team members (53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the subtheme of "channeling attention into productivity", participants found focusing on the present task, regulating responses to deadlines, unitasking and efficiently switching attention, all improved their productivity. Other studies, including a prior study of the MWPP, recognized improvements that mindfulness can bring to productivity (26). A workplace MBI improved team and organizational "climate" and individual performance with greatest improvements seen in co-operation between team members (53).…”
Section: Discussionmentioning
confidence: 99%
“…The massive open online course MWPP (25) was developed in 2015 by co-authors CH and RC from Monash University, Australia, and its development and delivery have been described in detail elsewhere (26). MWPP was delivered over four weeks via FutureLearn, a United Kingdom digital learning platform, although participants were free to complete the course at their own pace, within a 6 week window.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We added individual mindfulness as the moderator for two reasons. First, research has presented that mindful subordinates’ attention to the authoritarian management mode is intentionally open ( Bartlett et al, 2021 ); second, although creative deviance is risky, members with high individual mindfulness are more willing to take this risk to enhance team benefit ( Reb et al, 2015 ). A sample of 13 items is “I experienced my thoughts more as events in my mind than as a necessarily accurate reflection of the way things ‘really’ are.” The reliability coefficient of this individual mindfulness scale was 0.887.…”
Section: Methodsmentioning
confidence: 99%
“…Another point of importance is the provision of a physical activity place,( not rigorous exercise), evidence-based research has shown that patients with accessibility to places for walking (Morris & Hardman, 1997;Ouf et al, 2021;Visvizi et al, 2021), meditation (Goyal et al, 2014;Innes et al, 2012;Scott, 2022), yoga (Maddux et al, 2018;Shohani et al, 2018;Woodyard, 2011), and mindfulness (Bartlett et al, 2021;Mohammed et al, 2018) are prone to lower stress levels, lower pain levels and overall general improvement, than ones not partaking in these types of activities. This entails that designers design easily accessible areas that fit these types of activities, both inside and outside to accommodate for weather changes.…”
Section: Physical Attributesmentioning
confidence: 99%